2022
DOI: 10.1108/jsbed-02-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Resource type and SME alliance formation: the contingent role of perceived environmental uncertainty

Abstract: PurposeThe aim of the study was to determine how the different types of resources possessed by a small- and medium-sized enterprise (SME), in conjunction with the environmental uncertainty perceived by the SME's managers, affect SME's alliance formation.Design/methodology/approachPersonal interview method was used to collect responses to a survey instrument from Indian SMEs. Logistic regression technique was used to analyze the responses obtained from 127 manufacturing enterprises.FindingsThe study finds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Previous studies show managers have the difficult task of identifying and analyzing environmental uncertainty to adapt their firms to the new context (L opez-Gamero et al, 2011). A recent study by Prabhudesai et al (2022) analyzed 127 manufacturing enterprises in India Importance of networking capabilities and showed that managers' perceptions of environmental turbulence are key predictors of collaboration and alliance formation. Furthermore, perceived environmental uncertainties are a key factor in managing relationships (Mitrega and Pfajfar, 2015).…”
Section: Managers' Perception Of Environmental Uncertainties and Netw...mentioning
confidence: 99%
“…Previous studies show managers have the difficult task of identifying and analyzing environmental uncertainty to adapt their firms to the new context (L opez-Gamero et al, 2011). A recent study by Prabhudesai et al (2022) analyzed 127 manufacturing enterprises in India Importance of networking capabilities and showed that managers' perceptions of environmental turbulence are key predictors of collaboration and alliance formation. Furthermore, perceived environmental uncertainties are a key factor in managing relationships (Mitrega and Pfajfar, 2015).…”
Section: Managers' Perception Of Environmental Uncertainties and Netw...mentioning
confidence: 99%
“…On the other hand, Ferreira et al (2021) in their studies showed that strategic alliances provide a solution for small and medium scale enterprises to overcome intellectual capital resource limits, which has substantial implications for business practice. Prabhudesai et al (2022) in their studies found that while both tangible resources such as finances, component parts etc and intangible resources such as knowledge, expertise etc. have a favorable impact on an organization's ability to establish alliances, intangible resources have a far larger impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of alliance portfolio configuration, diversity is, thus, both a potential source of added value as well as a source of costly complexity (Kavusan and Frankort, 2019;Parkhe, 1991;Singh and Mitchell, 1996). In anticipation of such added costs, firms with more internal resources consequently have a clear advantage in configuring alliance portfolios (Prabhudesai et al, 2022). While small firms can gain competitive advantage through multiple, simultaneous alliances, the combinations and roles of different partners in the portfolio is an especially important determinant of whether the overall effect on performance is positive or negative (Baum et al, 2000;De Leeuw et al, 2014;Lee et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Alliance experience, however, is acknowledged to be a multifaceted concept which might have varying effects depending on its depth, breadth and a multitude of other factors (Duysters et al, 2012;Fern et al, 2012a;March et al, 1991;Rothaermel and Deeds, 2006). Few studies have focused upon small firms (for two notable exceptions see: Prabhudesai et al, 2022;Vicentin et al, 2021), where the "dark sides" of experience may be more pronounced due to biased behaviors, e.g. lack of adaptability to new information and overgeneralizing from limited experience (Fern et al, 2012b;March et al, 1991;Parker, 2006;Shepherd et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation